THE IMPACT OF THE POLYMORPHISM OF THE INTERLEUKIN-28 GENE ON THE COURSE OF THE СHRONIC EPSTEIN-BARR VIRUS INFECTION - Sorokina, O.G.; Liadova, T.I. (World of Medicine and Biology, 2017)
The family of herpes group viruses occupy one of the leading places in the structure of infectious diseases in terms of prevalence, the complexity of diagnosis and treatment. The Epstein-Barr virus (VEB) belongs to the Herpesviridae family and is a type 4 herpes virus. Infections caused by this virus are the most common and occupy an important place in the structure of diseases of herpesvirus etiology. As the results of epidemiological studies indicate, until reaching adulthood, approximately 90% of people are infected with VEB.The global spread of the VEB and the polymorphism of the symptoms makes it necessary to study this pathology in detail.The aim of this work was to study the impact of the polymorphism of the interleukin-28 gene on the course of the сhronic VEB-infection (CVEBI). We observed 158 people. 128 of them were patients with СVEBI, the main clinical manifestations of which were various immunopathological and immunodeficient conditions. Among the patients with СVEBI, two clinical groups were identified. Group I included 52 patients (40,6%) with frequent recurrences of СVEBI (3 or more exacerbations per year), as well as patients with persistently present clinical symptoms. In the II group 76 patients (59,4%) with rare recurrences of СVEBI (1-2 exacerbations per year) were included. The comparison group included 30 patients who had VEB - infection in anamnesis, but who did not have any complaints at the time of the study (group III).As a result of the conducted studies, we found that the dominant genotype of IL-28B rs12979860 is the СС genotype, which is more often detected in patients with rare recurrent СVEBI, and also in the comparison group. Analysis of the locus IL-28B rs8099917 allowed to establish a high frequency of verification of the TT genotype in patients with rare recurrences of СVEBI and in the comparison group, whereas in the group of patients with frequent relapses such combination was significantly less frequent. The frequency of non-random combination of alleles CC and TT at the locus rs12979860 and rs8099917, respectively, in patients with rare recurrences of СVEBI, as well as in the comparison group, was much higher than in the group of persons with frequent recurrences of СVEBI, while other combinations were much less common. As a result of the study, no combinations of the TT genotype at the locus rs12979860 IL-28B with the TT, TG and GG genotypes at the locus rs8099917 were found among the patients of the comparison group, whereas in the group of patients with СVEBI such combinations were noted, and in patients with frequent relapses such combinations were encountered more often. These combinations of genotypes possibly can be used in making the prognosis of the course of the disease.
Keywords: infectious mononucleosis; Epstein-Barr virus infection; genotype; cytokine; interleukin-28; the polymorphism of genes; frequency of relapses; prognosis